Effect of Cu2+ substitution on the structural properties of Mg-Mn nanoferrites. (2020) - Sharma, Rashmi; Pratap Singh, Virender; Kumar, Sahil; Sharma, Palvee; Singh, M.; Kumar, Gagan
Abstract: In the present work, we have successfully prepared Cu 2+ doped Mg-Mn nanoferrites using solution combustion (SC) method and we have mainly focused on the structural study of Mg0.9 Mn0.1 Cux Fe2-x O4 nanoferrite. There are many structural factors which affects the properties of the ferrites like particle size, stress, strain etc. The strain, particle size, stress and energy density have been analysed with the help of Williamsons-Hall Model using Uniform Deformation Model (UDM), Uniform Stress Deformation Model (USDM) and Uniform Deform Energy Density Model (UDEDM). The stress, strain, particle size & energy density have been found to reduce while lattice parameter, achieved from the Nelson-Riley plots, has been found to rise with the replacement of Fe 3+ ions by Cu 2+ ions.